Identifying longitudinal patterns of CPAP treatment in OSA using growth mixture modeling: Disease characteristics and psychological determinants - Yi, Huijie; Dong, Xiaosong; Shang, Shaomei; Zhang, Chi; Xu, Liyue; Han, Fang (Frontiers in Neurology, 2022)
In this study we aim to identify the distinct subtypes of continuous positive airway pressure (CPAP) user profiles based on the telemedicine management platform and to determine clinical and psychological predictors of various patterns of adherence. A total of 301 patients used auto-CPAP (Autoset 10, Resmed Inc.) during the treatment period. Four categories of potential predictors for CPAP adherence were examined : (1) demographic and clinical characteristics, (2) disease severity and comorbidities, (3) sleep-related health issues and (4) psychological evaluation. Then, growth mixture modeling was conducted using Mplus 8.0 to identify the unique trajectories of adherence over time. Adherence data were collected from the telemedicine management platform (Airview, Resmed Inc.) during the treatment. Three novel subgroups were identified and labelled “Adherers” (53.8% of samples, intercept=385, slope=-51, high mean value, negative slope and moderate decline), “Improvers” (18.6%, intercept=256, slope=50, moderate mean value, positive slope and moderate growth) and “Non-Adherers” (27.6%, intercept=176, slope=-31, low mean value, negative slope and slight decline). The comorbidities associated with OSA and the apnea-hypopnea index (AHI), which reflects the objective severity of the disease, did not differ significantly among the subgroups. However, “Improvers” showed higher levels of daytime sleepiness (8.1±6.0 vs. 12.1±7.0 vs. 8.0±6.1 in SWIFT, p=0.01) , reduced daytime function (4.6±1.6 vs. 3.8±1.6 vs. 4.2±1.8 in QSQ daytime symptoms, p=0.02) and characteristics of positive coping style (1.8±0.5 vs. 1.9±0.5 vs. 1.7±0.5 in SCSQ positive coping index, p=0.02). Negative emotion was more pronounced in patients with “Non-Adherers” (12.9±3.8 vs. 13.7±3.3 vs. 14.6±3.5, p=0.02 in the HADS depression dimension; 9.0±6.1 vs. 9.8±5.1 vs. 11.5±6.3, p=0.01 with Negative Affectivity in DS14, and 9.3±6.1 vs. 10.3±5.1 vs. 11.7±6.5, p=0.01 with Social Inhibition in DS14). Overall, our study demonstrated that CPAP therapy may present distinct trajectories of adherence over time in addition to the traditional binary classification. Self-reported sleep health issues (diurnal sleepiness and daytime dysfunction) as well as psychological characteristics (negative emotions and coping style) were predictors of different adherence subtypes in OSA patients. Understanding CPAP use profiles and their predictors enables the identification of those who may require additional intervention to improve adherence.